The Effects of Colors on The Human Mind in The Interior Design - I. R.Ibadullaev; S.B. Atoshov (Indonesian Journal of Innovation Studies, 2019)
This article discusses the types of colors, the colors in the interior of design, the color effects, and the negative and positive aspects of the color in the interiors